2013
DOI: 10.1016/j.jcss.2013.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Tractable counting of the answers to conjunctive queries

Abstract: Abstract. Conjunctive queries (CQs) are one of the most fundamental forms of database queries. In general, the evaluation of CQs is NPcomplete. Consequently, there has been an intensive search for tractable fragments. In this paper, we want to initiate a systematic search for tractable fragments of the counting problem of CQs, i.e., the problem of counting the answers to a CQ. We prove several new tractability and intractability results by starting with acyclic conjunctive queries and generalising these result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(73 citation statements)
references
References 25 publications
1
72
0
Order By: Relevance
“…Already for acyclic conjunctive queries the combined complexity is #P -complete [25] and only the quantifier free acyclic conjunctive queries can be solved in time linear in ||D|| [3]. Adding just one quantifier already make already the problem hard [26].…”
Section: Counting the Number Of Solutionsmentioning
confidence: 99%
“…Already for acyclic conjunctive queries the combined complexity is #P -complete [25] and only the quantifier free acyclic conjunctive queries can be solved in time linear in ||D|| [3]. Adding just one quantifier already make already the problem hard [26].…”
Section: Counting the Number Of Solutionsmentioning
confidence: 99%
“…On bounded-arity queries and if no projection is allowed, counting is known to be tractable over a class C if, and only if, queries in C have bounded treewidth [12,17]-hence, cores play no role here. Moreover, without projections, most commonly considered structural restrictions generalizing acyclicity yield tractable counting problems, even without fixing any arity bound [35]. However, in almost all practical applications, there are variables that are crucial to join different relations in the query, but that are irrelevant to the user, i.e., they are not required in the output and their instantiations must not be counted.…”
Section: Structural Decomposition Methodsmentioning
confidence: 99%
“…• Pichler and Skritek [35] observed that classical decomposition methods are not helpful when projections are allowed. Indeed, they showed that counting answers is #P-hard in this case, even for acyclic queries.…”
Section: Structural Decomposition Methodsmentioning
confidence: 99%
“…The result is also tight on recursively enumerable classes of instances having bounded arity (unless FPT = W [1]) [19]. Moreover, in the general case of classes of instances having bounded hypertree width and with arbitrary sets O of desired variables, the problem is still tractable if either the constraint relations or the constraint scopes have a fixed maximum size [70].…”
Section: Theorem 43 ([48]mentioning
confidence: 99%